Strengthening Cocoa Farmers’ Capacity for EUDR Compliance: A Policy Review of Agricultural Education and Extension in Indonesia - Muhammad Obie (Kirana Publisher (KNPub), 2026)
The European Union Deforestation Regulation (EUDR) presents significant challenges for cocoa-producing countries by requiring compliance with strict standards related to traceability, geolocation, and deforestation-free production. As a major cocoa producer, Indonesia must strengthen the capacity of smallholder farmers to meet these emerging sustainability requirements. This study aims to review the role of agricultural education and extension policies in supporting cocoa farmers’ readiness for EUDR compliance. A policy review approach was employed using secondary data obtained from academic publications, government regulations, policy documents, and reports from international organizations related to agricultural education, extension services, sustainability governance, and cocoa development. Data were analyzed through thematic content analysis to identify policy priorities, implementation challenges, and capacity-building opportunities. The findings indicate that agricultural education and extension systems play a crucial role in enhancing farmers’ knowledge, environmental awareness, digital literacy, and traceability capabilities. However, existing policies remain constrained by limited institutional coordination, unequal access to extension services, and insufficient integration of EUDR-related competencies into farmer training programs. Strengthening policy coherence, expanding sustainability-oriented extension initiatives, and promoting digital learning mechanisms are essential for improving farmers’ preparedness. This study contributes to the literature on agricultural education and provides policy recommendations for supporting sustainable cocoa production and EUDR compliance in Indonesia.